Identification of Conversation-based Audio Recordings Between Co-Car Drivers and Passengers - Wahyu Setiawati (Universitas Muhammadiyah Mataram, 2018)
Go-Car is part of Go-Jek service that provides varied online services to its passengers. In this paper, the driver is the part of its online taxi service. The aim of this paper is to find out the types of identity that appear during a short conversation between a Go-Car driver and the passengers. The paper used the framework of conversational identity to examine the twelve-minute audio recording of the conversation to find the type of identity that is negotiated in driver’s talk. The conversation is situated naturally in the road to Mataram city. As the results, two types of identity appeared in Go-Car Driver’s talk, namely, personal identity and collective identity. The personal identity expression could be seen from the way the driver showing his status as a bank staff and a highly paid Go-Car driver.